Impact of Physical Activity on Academic Achievement of Secondary Level Students in Kathmandu (Interdisciplinary Research in Education, 2024)
This study aims at exploring the impact of physical activity on the academic achievement of secondary-level students in Kathmandu District, Nepal. Cross-sectional research design was used, and data were collected from 31 students of grade nine and ten studying at Pushpa Kunja High School through structured questionnaires. The results reveal an inverse relationship between physical activity and academic performance. Solo activities like running and walking positively affected academic achievement, while team sports and yoga showed inconsistent trends. A statistically significant negative correlation was also found between the intensity of physical activity and academic performance (r = −0.392, p = 0.029). It means; higher the students' achievement level, lesser the participation in vigorous activities. This would challenge the assumption of a universally positive relationship between physical activity and academic achievement and also highlights the importance of balancing them for good academic achievement. This study, therefore, calls for specific school-based interventions to ensure optimal physical activities for holistic development, considering the unique cultural and infrastructural factors related to Nepal's education system.